Analisis Faktor Eksternal yang Mempengaruhi Beban Kerja Kelompok Penyelenggara Pemungutan Suara pada Pemilihan Umum 2019 - Santi Hariati; Muhammad Arif Nasution; Warjio Warjio (PERSPEKTIF, 2021)
This study aims to analyze external factors, namely tasks, work environment, and work organization that affect the workload of KPPS in the 2019 General Election in Binjai Utara District, Binjai City. This study uses a quantitative method because it analyzes external factors that affect workload with independent / independent variables (X), in this study are external factors that affect workload, namely tasks (X1), work environment (X2) and work organization (X3). ; The dependent / dependent variable (Y) is the workload of the 2019 Election KPPS officers in Binjai Utara District, Binjai City. The results of the research and discussion obtained by the assignment had a positive and significant effect on the workload of KPPS in the 2019 Election in Binjai Utara District, Binjai City, so that Hypothesis 1 was accepted; the work environment has a positive and significant effect on the workload of KPPS in the 2019 Election in Binjai Utara District, Binjai City, so that Hypothesis 2 is accepted; Work organizations have a positive and significant influence on the workload of KPPS in the 2019 Election in Binjai Utara District, Binjai City, so Hypothesis 3 is accepted. The researcher concluded that the assignment has a positive effect, HaHypothesis 1 is accepted; work environment has an accepted influence. Hypothesis 2; Work organization has a positive influence, HaHypothesis 3 is accepted.